Pengaruh Suhu Modifikasi Heat Moisture Treatment (HMT) Terhadap Karakteristik Fisikokimia Tepung Biji Mangga Arum Manis (Mangifera indica L.) - Mardani, Desak Nyoman Savita; Wiadnyani, Anak Agung Istri Sri; Permana, I Dewa Gde Mayun (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 14 No 2 (2025): Jurnal ITEPADO - 10.24843/10.24843/itepa.2025.v14.i02.p12, 2025)
Horticultural waste such as mango seeds, is a significant waste stream in Indonesia with high potential for utilization due to its high starch content. However, flour derived from mango seeds has limitations in food industry applications due to suboptimal physicochemical properties. This study aimed to analyze the effect of Heat Moisture Treatment (HMT) temperatures on the physicochemical characteristics of mango seed flour and determine the optimal HMT temperature for producing flour with the best characteristics. The study employed a Completely Randomized Design (CRD) with five levels of HMT treatment temperatures: P0 (no modification), P1 (80°C), P2 (90°C), P3 (100°C), and P4 (110°C). Data were analyzed using Analysis of Variance (ANOVA) followed by Duncan’s Multiple Range Test (DMRT) at a 5% confidence level. The results indicated that HMT significantly influenced the physicochemical properties of mango seed flour, including starch content, amylose content, solubility, swelling power, viscosity, and color. The P4 treatment (110°C) produced the best flour condition with the lowest moisture content (5.78±0.12%), the highest starch content (33.32±0.8%), the highest amylose content (22.12±0.57%), and the highest solubility (7.03±0.33%), as well as a swelling power of 3.66 g/g and color characteristics (L* 68.45, a* 4.44, b* 8.62). In terms of amylography, P4 has a peak viscosity of 85 cP and a final viscosity of 63 cP stable.